2016
DOI: 10.3356/rapt-50-01-76-83.1
|View full text |Cite
|
Sign up to set email alerts
|

Species Identification of Golden and Bald Eagle Talons Using Morphometrics

Abstract: The Golden Eagle (Aquila chrysaetos) and Bald Eagle (Haliaeetus leucocephalus) are the largest avian predators in North America, and are thus species of great ecological importance and cultural significance. There is a long history of human use of eagle body parts, and this use continues today: Bald and Golden eagles are among the North American birds most affected by the illegal wildlife trade. Detached eagle talons are often recovered in both law enforcement and archaeological contexts, but data to allow mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 13 publications
(13 reference statements)
0
4
0
Order By: Relevance
“…Bald and Golden Eagles have long been identified based on morphological characters and measurements (e.g., wing chord, exposed culmen, tarsus, middle toe length) taken on live individuals and complete specimens (Chandler 1916, Friedmann 1950, Bortolotti 1984, Clark and Wheeler 1987, Pyle 2008, Appleton et al 2016, Ely and Hallett 2021). However, few studies have attempted to identify the feathers and other parts of eagles commonly found in the wildlife trade.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Bald and Golden Eagles have long been identified based on morphological characters and measurements (e.g., wing chord, exposed culmen, tarsus, middle toe length) taken on live individuals and complete specimens (Chandler 1916, Friedmann 1950, Bortolotti 1984, Clark and Wheeler 1987, Pyle 2008, Appleton et al 2016, Ely and Hallett 2021). However, few studies have attempted to identify the feathers and other parts of eagles commonly found in the wildlife trade.…”
Section: Resultsmentioning
confidence: 99%
“…Species identifications are used in many practical investigations: anthropological or museum studies (Corbino et al 2022), bird strikes (Laybourne 1974, Brom 1986), fossilized feather identifications (Laybourne et al 1994, Dove et al 2010), and law enforcement and forensics (Trail 2003a). The morphological differences between the two North American eagle species are well documented (Wheeler 2003, Pyle 2008, Buehler 2020, Katzner et al 2020), as is their utility for identification in a forensic context (e.g., bones [Trail 2017], talons [Appleton et al 2016], and feathers [Trail 2014, Trail and Gaffney 2021]).…”
Section: Introductionmentioning
confidence: 99%
“…The situation is only slightly better in North America, where there is one publication facilitating the identification of local species (Mosto & Tambussi, 2014). There are some studies on talons of European birds of prey but they focus on morphological adaptations to various habitats and predator-prey relations, and they analyze entire digits with horny sheats (e.g., Appleton et al, 2016;Csermely & Rossi, 2006;Musindo, 2006), which do not preserve in archeological deposits. The only other papers that include bony cores of talons are those that describe fossil birds, often as old as the Paleogene (e.g., Mayr, 2006aMayr, , 2006b.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, comparatively little information is available on the identification of the bones of bald and golden eagles (but see Appleton et al 2016 for identification of detached eagle talons). Skeletal remains are sometimes the only material recovered in avian mortality surveys, due to the effects of decomposition and exposure.…”
Section: Introductionmentioning
confidence: 99%